(untitled) (Research, Society and Development, 2021)
For the promotion and protection of health, food and nutrition are considered basic requirements, since they make it possible to affirm the potential for human growth and development with quality of life. In recent years, the substitution of homemade and natural food for industrialized foods, affecting the general population, negatively influencing the health / disease process. This review aims to explain how probiotics can affect chronic diseases. Scientific bases such as Scielo, Pubmed and Periodicos were used, in which the articles that best fit the theme were selected. This work showed the importance of probiotics for chronic diseases and also the need for further research for further scientific confirmation.